2022
DOI: 10.1136/bmjophth-2021-000744
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and complications in infantile cataract surgery: a real - world scenario

Abstract: ObjectiveTo evaluate visual outcomes and complications of infantile cataract surgery through a 1-year follow-up period in a real world scenario.Methods and analysisProspective observational study evaluating infants with cataract undergoing surgery.ResultsWe analysed 173 eyes of 97 infants (76 bilateral); median age 18.7 weeks, (IQR: 11–33.9 weeks). Toxoplasmosis, rubella, cytomegalovirus and herpes infection was the most common aetiology in both unilateral 10 (47.6%) and bilateral 43 (55.1%) cases, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…12 Visual axis opacification is the most common complication following paediatric cataract surgery. [13][14][15][16][17] In Choudhary S et al 2017 9 it was present in 75% of eyes, which did not undergo PPC, developed PCO while only 11.76%, which underwent PPC, developed PCO. In our study it was seen in 36% of cases which did not undergo PPC develop PCO.…”
Section: Resultsmentioning
confidence: 99%
“…12 Visual axis opacification is the most common complication following paediatric cataract surgery. [13][14][15][16][17] In Choudhary S et al 2017 9 it was present in 75% of eyes, which did not undergo PPC, developed PCO while only 11.76%, which underwent PPC, developed PCO. In our study it was seen in 36% of cases which did not undergo PPC develop PCO.…”
Section: Resultsmentioning
confidence: 99%
“…The 1-year results of this cohort are reported by the authors previously. [ 9 ] Of 97 patients who were operated, 94 (96.9%), 91 (93.8%), 65 (67.0%), and 79 (81.4%) followed up at 1 week, 1 month, 6 months, and 1 year, respectively. The mean age at surgery was 23.7 weeks (median: 18.7 weeks and interquartile range [IQR]: 11–33.9 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…The study design, the baseline patient demographic details, the preoperative evaluation techniques, surgical techniques, factors influencing IOL implantation, choice of IOL, postoperative eye care regime, patching and optical correction regimens, and postoperative evaluation methods have been reported previously along with visual and refractive outcomes and complications at 1 year after infantile cataract surgery. [ 9 ] Eyes that satisfied the preoperative criteria of an axial length ≥16.5 mm and a horizontal corneal diameter ≥10.5 mm, in the absence of anterior segment dysgenesis and glaucoma, were implanted with an IOL in the bag (AcrySof SA60AT, Alcon Laboratories, Inc, Fort Worth, Tx USA). [ 10 ] The IOL power was calculated using the Sanders–Retzalff–Kraff II/T formula with Enyedi’s guidelines for under-correction.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there has been a debate about intraocular lens implantation in children younger than 2 years, and several studies concerning this issue have been performed (e.g. Chattannavar et al., 2022, Infant Aphakia Study Group, 2010, Solebo et al., 2015). The 5‐year results of the IOLunder2 study (Solebo et al., 2018), where primary IOL implantation was performed in 88 of 158 eyes (56%) in children under 2 years of age, showed that implantation had no advantage in terms of visual outcome or glaucoma risk but carried a significantly increased risk of VAO requiring surgery under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%